Alkali-silica reaction in alkali-activated combined slag and fly ash concretes: The tempering effect of fly ash on expansion and cracking. (10th August 2020) - Rodrigue, Alexandre; Duchesne, Josée; Fournier, Benoit; Champagne, Mathieu; Bissonnette, Benoit
Highlights: Increasing FA% in alkali-activated slag/FA concrete results in decreasing DRI values. Expansion and DRI values are coherent and evaluate adequately the level of damage. ASR-type secondary products were observed with pseudo rosette-type microtextures. Pore solutions of slag/FA pastes specimens show high concentrations of sodium. Pore solutions of slag/FA pastes specimens show negligible calcium concentrations. Abstract: This research has shown that increasing the fly ash (FA) content in alkali-activated slag slag/FA systems results in decreasing expansion of concrete prisms incorporating moderately to highly-reactive aggregates. The internal damage in the above prisms, as determined through the Damage Rating Index (DRI), correlates well with expansion, ranging from marginal (40% FA/60% Slag; two-year expansions < 0.011%) to high (100% Slag; two-year expansions from 0.12 to 0.15%). Scanning electron microscopy (SEM) and Energy Dispersive X-ray analysis (EDS) confirmed the presence and distribution patterns of ASR-like reaction products in the alkali-activated concretes. The pore solution of alkali-activated slag/FA companion paste specimens showed high sodium concentrations but negligible calcium (essential to ASR) concentrations, thus likely explaining, along with limited internal moisture access, the limited concrete prism expansions observed in such systems.